MELAYANI DENGAN HATI: Menghapus Diskriminasi dan Segregesi antara Anak Reguler dengan Anak Berkebutuhan Khusus melalui Sekolah inklusif YBPK Kota Kediri - Hanur, Binti Suaidah; Avif, Sholeh (Jurnal al Hikmah, 2018)
Inclusive Education is an education which provides education for all students and gives the equal chance for all students in the same class. Each students is given chance to help, to take and give, to share each other although each of them has the differences could be in the ability or in the capability, mentally or physcally. Though, the concept of inculsive education had been existed in the early of 1900s but there was misunderstanding in applying the concept. This was related to the concept of classification or labelling by which it tends to two paradoxs term, they are regular students and special needs students. Then it affects the process and the output of each students. Students who is labelled by “idiot” will cause discrimination and segregation problem toward students. Hereby, this research was focused on how the methods applied in the learning process in PAUD Inklusif could be proved eliminate the discrimination and segregation problem between reguler students and special needs students and also how the assessment system applied in the PAUD Inklusif can improve the special needs students’ achievement